2011
DOI: 10.1074/jbc.m111.303891
|View full text |Cite
|
Sign up to set email alerts
|

Lowered Expression of Heparan Sulfate/Heparin Biosynthesis Enzyme N-Deacetylase/N-Sulfotransferase 1 Results in Increased Sulfation of Mast Cell Heparin

Abstract: Background: NDST1 and 2 are isoenzymes taking part in heparan sulfate and heparin N-sulfation during biosynthesis. Results: NDST1ϩ/Ϫ and NDST1 Ϫ/Ϫ mast cells synthesize heparin with increased degree of sulfation. Conclusion:Tentatively, the Golgi enzyme complex, "the GAGosome," responsible for heparin biosynthesis, is more efficient when containing only NDST2. Significance: Learning how biosynthesis is regulated is crucial to understanding the biological functions of heparin/heparan sulfate.Deficiency of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 47 publications
0
15
0
2
Order By: Relevance
“…6B ) may be protective 50 . Selective changes in disaccharide content may also be specific to individual cells as mast cell responses have demonstrated altered HS content with Ndst1 deficiency 51 . Studies reported by other groups do support a pro-inflammatory function for some GAGs.…”
Section: Discussionmentioning
confidence: 99%
“…6B ) may be protective 50 . Selective changes in disaccharide content may also be specific to individual cells as mast cell responses have demonstrated altered HS content with Ndst1 deficiency 51 . Studies reported by other groups do support a pro-inflammatory function for some GAGs.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin and chondroitin sulfate analysis by RPIP-HPLC was performed as described previously [26] with 5 x 10 6 BMMCs cultured either under normal copper conditions, excess copper (20 μM) or were deprived of copper (BCS: 200 μM).…”
Section: Methodsmentioning
confidence: 99%
“…To this end we used an approach where the glycosaminoglycan (GAG) side chains of the proteoglycans were depolymerized to disaccharide units by enzymatic digestion, followed by HPLC separation to determine the structure of the respective disaccharides (26). This structural analysis revealed that chondroitin sulfate (composed of repeating disaccharide units of the general structure: hexuronic acid (HexA)-N-acetylgalactosamine (GalNAc)) was the main type of GAG produced by both WT and Ctr2 −/− BMMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Heparin and chondroitin sulfate analysis by RPIP-HPLC was performed with 5 × 10 6 cells as described previously (26). …”
Section: Methodsmentioning
confidence: 99%